Core remodeling leads to long wavelength fluoro-coumarins. Issue 28 (3rd July 2020) - Matikonda, Siddharth S.; Ivanic, Joseph; Gomez, Miguel; Hammersley, Gabrielle; Schnermann, Martin J.
Abstract : Fluoro-Coumarins are a novel class of far-red and near-infrared solvent sensitive dyes of exceptionally low molecular weight. Abstract : Low molecular weight, uncharged far-red and NIR dyes would be enabling for a range of imaging applications. Rational redesign of the coumarin scaffold leads to Fluoro-Coumarins (FCs), the lowest molecular weight dyes with emission maxima beyond 700, 800, and 900 nm. FCs display large Stokes shifts and high environmental sensitivity, with a 40-fold increase in emission intensity in hydrophobic solvents. Untargeted variants exhibit selective lipid droplet and nuclear staining in live cells. Furthermore, sulfo-lipid derivatization enables active targeting to the plasma membrane. Overall, these studies report a promising platform for the development of biocompatible, context-responsive imaging agents.